Impact of lockdown on children with type-1 diabetes: returning to the community was associated with a decrease in HbA1c - Morat, Benjamin; Lucidarme, Nadine; Gibert, Auriane; Harbulot, Carole; Lachaume, Noémie; Gréteau, Stéphanie; Basmaci, Romain (Frontiers in Pediatrics, 2023)
Background In March 2020, a 2-month lockdown of the entire population has been declared in France to limit the spread of COVID-19. Sudden changes in daily life can impact the glycemic control of patients with type 1 diabetes (T1D), especially children and adolescents. We aimed to assess the impact of the lockdown on glycemic control in children and adolescents with T1D. Methods Children with T1D were prospectively recruited in two pediatric centers from May 11 to August 1, 2020. At inclusion, patients and/or parents were asked to fill in a form assessing the patient's lifestyle during the lockdown and a medical case report form was filled in by clinician. The mean of the three last glycated hemoglobin (HbA1c) values obtained before lockdown (HbA1c_mean; before March 17, 2020) was compared to the first HbA1c value measured after the lockdown (HbA1c_after; from May 11 to August 1, 2020). Univariable and multivariable analyses were performed, as appropriate, to identify factors associated with glycemic changes during lockdown. Results One-hundred-and-eighteen children and adolescents (median age was 14.1 years, 50% males) with T1D (median time from diagnosis was 4.1 years) were enrolled in the study. No significant difference was observed between medians of HbA1c_mean and HbA1c_after values (8.37% [7.88; 9.32%] vs. 8.50% [7.70; 9.50%], respectively; p = 0.391). Returning to the community was a protective factor [OR 0.31 (0.09–0.94); p = 0.045]. Patients having increased HbA1c were more frequently in contact with a suspected case of COVID-19 [OR 9.07 (2.15–53.66); p = 0.006], whereas patients having decreased HbA1c had the feeling of increase number of hypoglycemia [OR 0.19 (0.05–0.57); p = 0.006]. Conclusion In our patients, HbA1c before and after the lockdown was stable. In subgroup analysis, returning to the community was a protective factor. In addition, feeling of hypoglycemia was more frequent in the patients with decreased HbA1c.